The Influence of Executive Compensation and Executive Shares Ownership towards Corporate Tax Avoidance - Melisa Rahardja Tandiono; Setyarini Santosa (JAAF (Journal of Applied Accounting and Finance), 2021)
This study aims to examine the influence of executive compensation and executive shares ownership towards tax avoidance. By knowing the influence of executive compensation and executive shares ownership towards tax avoidance, it could be an input for better regulations relates to tax avoidance. This study used the annual report of property, real estate, and building construction company listed on Indonesia Stock Exchange during 2014-2018. This study uses purposive sampling to determine the samples. There are 14 companies used in this research, in total there are 70 annual reports as samples used in this research. The control variables used in this research are company performance proxied using return on asset and company size proxied using total asset. The method used in this research is multiple linear regression. This study found that executive compensation has significant influence with negative coefficient on tax avoidance and executive shares ownership does not influence tax avoidance.